Changes of agriculture land use in Kelantan river basin from 2004 to 2015 using time series satellite images - Nazri, Mohd Zahrulnaim (2016)
Agriculture is Kelantan’s main economic activity while most of fruit farmers are located in Kelantan, with rice, rubber and tobacco is the state’s foremost agricultural produces. Besides, fishing and forestry are also major contributors to the economy. However, flood is one of the most common natural disaster in Kelantan. During the monsoon season, Kelantan is likely to face flood problem. From 453,958 ha of agriculture in whole Kelantan, 177,257 ha is susceptible to flood. Flood is major factor that causes losses in socio-economic aspects of human life. The heavy rainfalls increase the water inundation area and affect economic and agriculture sector. Due to the annual flooding events, some of the agricultural areas that are prone to flood may have changed over the years. In 2014, the agriculture sector in Kelantan recorded about RM105 million in losses to the massive floods. Therefore this study is conducted to analyse the changes of agricultural land use as affected by the flood events in the Kelantan River Basin since 2004 to 2015, and also to determine if time series SPOT images can be used to map the changes of agricultural land use. The land use and the land cover between those years were compared. In order to see the changes, the image processing involves several processing steps such as histogram matching / normalization, and classification. As the expected result, we can see the changes agriculture land use in Kelantan River Basin from 2005 to 2015 using the SPOT satellite images because it has the ability to measure reliable spatial and temporal photosynthetic activity and canopy structural variations.